Developing active chitosan-based edible film for extending the shelf life of guacamole - Mora-Sánchez, Monserrat; Hernández-Carranza, Paola; Ramírez-López, Carolina; Ruiz-López, Irving Israel; Ochoa-Velasco, Carlos Enrique (Frontiers in Sustainable Food Systems, 2023)
This study aimed to evaluate the effect of edible films (EFs) on important parameters of fresh guacamole and to select the best EF for evaluating its stability and protection effect after 28 days of storage (4 and 20°C). EFs based on chitosan (2%), glycerol (1%), citric acid (1.5-2.5%), and lemon-onion extract (0-2%) were applied on the surface of fresh guacamole to evaluate its effect in its color, microbiological and antioxidant properties after 48-h storage (4 and 20°C). Results indicated that EFs delay the total color change and increase the antioxidant capacity of guacamole, while the microbial count was less than 100 CFU/g and 10 CFU/g for mesophylls and molds plus yeasts, respectively. According to the lowest total color change (7.93 -14.92) and highest antioxidant capacity (1201.22 mg Trolox/100g), EF1 (2% chitosan, 1% glycerol, 1.5% citric acid, and 2% lemon-onion extract) was selected for its analysis during the storage. After 28-d storage at 4 and 20°C, a slight change in the physical characteristics of the EF was observed, while microbial load and antioxidant properties remained constant. Moreover, the selected EF maintains its capacity to avoid guacamole browning, being well-accepted by the consumer (I like -I like much), who did not detect the application of EF, even after 24-h of its application onto the fresh guacamole. Results presented in this study indicated that developed EF maintained the quality characteristics of guacamole, and its effect did not change after 28-d storage.